Introduction - Anne Hess, Jana-Katharina Burnikel, Joachim Frenk, (Journal of Posthumanism, 2024)
In parallel to the evolution of the multivocal critical debate around it, the posthuman has increasingly invaded everyday life over the last 50-odd years. In the 2020s, posthuman encounters are, for large parts of humanity, occurrences in multiple areas of everyday life. The number of artificially created entities, some of which are ever more indistinguishable from their human creators, has multiplied. The human body has become the focal point of enhancements that call hitherto largely unchallenged notions about its humanness into question, from prosthetic joint replacements and the medical procedures enabling them to the promises of genetic engineering and neurotechnology.